(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Effective investing requires the constant introduction of new projects. Lack of progress can lead not only to a decrease in company performance, but also to a loss of competitiveness of the products and services offered. Investment knowledge therefore remains important. This article covers the basics of investing, including the definition of an investment, its objectives, and the steps and analysis of the investment process.